Kebijakan Hukum Pidana Terhadap Tindak Pidana Ujaran Kebencian (Hate Speech) di Media Sosial - Kade Richa Mulyawati (Kertha Wicaksana, 2021)
Technological advances that are developing very rapidly not only have a positive impact on people's lives but also have a negative impact. The ease of freedom of expression by relying on technology brings new developments in types of crime, namely hate speech on social media in the form of typed or video. If this is not regulated further, it will be very worrying, people will cross the line and will cause discomfort or feeling offended by a certain person or group. Criminal law has certainly paid attention to the consequences that will be faced by someone who intentionally or unintentionally commits this crime of hate speech. In this article, we will discuss how criminal law views hate speech crimes and will also discuss how the proof system in this hate speech crime is. The method used is normative legal research which is carried out by examining library materials and the approach used is a legislative approach related to hate speech crimes. The results and discussion obtained are that if we look at the Criminal Code and other laws and regulations, several articles that can be imposed on someone who commits hate speech have been explained. Articles that regulate actions regarding hate speech against a person, group or institution based on the Circular Letter of the Chief of Police No: SE/06/X/2015 are contained in Article 156, Article 157, Article 310, Article 311, then Article 28jis. Article 45 paragraph (2) of Law Number 19 of 2016 concerning information and electronic transactions and Article 16 of Law No. 40 of 2016 concerning the elimination of Racial and Ethnic Discrimination. regulated in the Criminal Code.